Screening of Antibacterial Properties for Some Iraqi Plants Against Salmonella typhimurium: Salma N. Malik , Huda J. Mohammed ,Janet Arshak Misak - Mohammed, Huda J. (The Iraqi Journal of Veterinary Medicine, 2011)
This study was include the investigation of the antibacterial activity of ethanolic extract for (12) type of Iraqi plant leaves (Allium porrum L, Apium graveolens Mill., Cassia angustifollia Vahl., Lawsonia inermis L., Lepidium sativum L., Malva sylvestris L., Monthapiperita L., Ocimmum bassillicum L., Pettroselinum crispum Mill., Raphanus sativus L., Sponacia oleraceal. and Trigonella foenum L.). In different concentrations (20, 40, 60, 80, 100) mg/ml against Salmonella typhimurium in vitro using agar well diffusion method. All ethanolic extract of leaves showed a high activity against this bacterium except of Cassia angustifollia Vahl. as compared with the other extracts. The ethanolic extract of leaves of Petroselinum crispum Mill was showed the best activity with inhibition zone of twenty three mm in the concentration (100) mg/ml. This results confirm the antibacterial activity of these plants, and leaf components which are responsible for this action have to be isolated for using as therapeutic agents.Conclusion: The present investigation together with previous studies provide support to the anti-Salmonella typhimurium properties of studied plant leaves. It can used as antibacterial supplement towards the development of the new chemotherapy . Additional in vivo studies and clinical trails would be needed to justify and further evaluate the potential of these plants as anti-Salmonella typhimurium agent in treatment of infectious diseases caused by this bacteria.